Report by Professor D'Arcy Thompson on his mission to the Behring Sea in 1896, dated March 4, 1897 [electronic resource]. - Thompson, D'Arcy Wentworth, 1860-1948 ([S.l. : s.n., 1897)
Tables. Original issued in series: [Command papers / Great Britain. Parliament] Cd. 8426. Electronic reproduction. Mode of access: Internet. 44